Life threatening complications after unsuccessful attempt of the guidewire dilating forceps tracheostomy in multi-trauma patient with cervical spine injury - Bartolek, Dubravka (Array, 2009)
Abstract: Percutaneous tracheostomy (PCT) is a safe method under proper patient selection, increased technical experience and bronchoscopy- or ultrasound-guided procedure. Trauma patients with cervical spine fractures and spinal cord injury are at a high risk for respiratory failure and require a definitive airway followed by prolonged mechanical ventilation. We would like to present multiple, life- threatening complications after unsuccessful attempt of the guidewire dilating forceps tracheostomy (GWDF) in one trauma patient with a cervical spine injury. With this case report we would like to lay emphasis on the importance of continuously bronchoscopy- or ultrasound-guided PTC in trauma patients, especially with cervical spine injury, as the need to respect the steep-learning curve in its performance